The integration of plantation crops with timber species in Malaysia / Ahmed Azhar Jaafar ... [et al.] - Jaafar, Ahmed Azhar; Kasiran, Norman; Muhammed, Suhaimi; Wan Ismail, Wan Hanisah (Faculty of Applied Sciences, 2004)
Agroforestry activities were studied focusing on the integration of plantation crops (oil palm and rubber) with timber species (sentang and teak). The study involves government and private agencies and farmers practicing this type of agroforestry activities. It has been found that the most common type of integration involves rubber and sentang implemented by smallholder farmers to supplement the low income generated by rubber especially during the low productive periods and during replanting of the main crops. The study has shown that most respondents applied the normal agricultural management practices as in monocrops but has not experienced any adverse effects in relation to plant growth and yield (crops and timber trees). This indicates that integration of crop plants and timber species is a viable approach to improve farm income. However the respondents do indicate the need for more technical advice from related agencies to improve the implementation of their integration programs and acquire better outcomes in terms of yield and income.